The use of Mangrove Crab (Scylla sp.) shell chitosan as heavy metal lead (Pb) adsorbent - Zette, Ilma Fistannisa; Nugroho, Andhika Puspito (2014)
Heavy metal pollution of lead (Pb) in the environment can be addressed by lowering the concentration of Pb using adsorption techniques. Chitosan is a biopolymer chitin deacetylation modifies it into a potential heavy metal adsorbent. One source is the chitosan shell from mud crab (Scylla sp.) common as household eating waste. This study aims to determine the efficiency of the use of mud crab shells as raw material for chitosan and to determine the most optimal chitosan concentration and stirring time for the adsorption of Pb. Isolation of chitin done with deproteination and demineralization of mud crab shell powder. Chitosan is obtained from chitin deacetylation. Adsorption by chitosan performed on 27 samples of 1 ppm Pb 10 ml with chitosan concentration variation of 0.1;0.3;0.5 grams and stirring time for 5;10;15 minutes. Determination of heavy metal content in the samples was done using Atomic Absorption Spectrophotometer (AAS). The results showed that the efficiency of the mangrove crab shell chitosan as raw materials amounted to 29.67%. The most optimal chitosan concentration and stirring time for 1 ppm Pb adsorption is 0.5 grams chitosan with 15 minutes stirring time.